Clinical Practice Guidelines for Potential Donors Management - José Roque Nodal Arruebarrena; José Noel Marrero Rodríguez; Yenisey Quintero Menéndez; Aida M. Reyes Pérez; Julio Jova Dueñas (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Clinical Practice Guidelines for Potential Donors Management. It has been defined as the patient in Glasgow coma with scale higher or equal to 8 who doesn´t present contradictions for transplant (possible donor) and who has been diagnosed of encephalic death. This document reviews and updates concepts, lists indications and contraindications for different organs donation, clinical assessment of the donor and its treatment. It includes assessment guidelines focused on the most important aspects to be accomplished.